CURAHAN WAKTU KERJA DAN PENGAMBILAN KEPUTUSAN WANITA KELUARGA PETANI KELAPA SAWIT POLA PLASMA DI DESA SARI GALUH KECAMATAN TAPUNG KABUPATEN KAMPAR - Ernita Zahira Muttaqin; Rosnita '; Yusmini ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objective of this research is : 1) Analysis the amount of working time of woman in the household and productive business of Nucleus Estate Smallholder (NES) farmer family. 2) Knowing the factors that affect the working time of woman in Nucleus Estate Smallholder (NES) farmer family. 3) Knowing the pattern of decision-making of woman in Nucleus Estate Smallholder (NES) farmer family. The research used a survey method and sampling as many as 32 samples. Analysis of the data using Ordinary Liest Square (OLS) and Likert Scale’s Summated Ratting (SLR). The result showed that the average working time of productive woman in the village of Sari Galuh is high at 33,74 hours / week when compared to average of household working time of woman are only 22,82 hours / week.The factors that affect working time is age factor, experience working factor and family dependents factor. The pattern of family decision making is dominated by a woman or a farmer’s wife. Keywords: working time, decision-making, Nucleus Estate Smallholder (NES)